Analysis of symptom cluster and influencing factors for patients with gynecological cancer during chemotherapy (妇科恶性肿瘤化疗患者症状群及影响因素调查研究) - TIAN Yaling (田亚林); WANG Qingtian (王庆天); ZHANG Jinjing (张金晶); DENG Nan (邓楠); YANG Mingqian (杨明倩); WANG Xue (王雪) (Journal of International Translational Medicine Limited, 2022)
Objective To investigate the related symptoms, symptom cluster and influencing factors among patients with gynecological cancer during chemotherapy. Methods A total of 430 inpatients with gynecological cancer treated by chemotherapy were investigated by using the General Information Questionnaire and Chinese version of M. D. Anderson Symptom Inventory (MDASI). Results There were many symptoms in gynecological cancer patients during chemotherapy. The top three symptom incidence were vomiting (91. 86%), drowsiness (90. 70%) and fatigue (90. 00%). The top three incidence of symptomatic distress were walking (76. 74%), interpersonal (76. 30%) and emotion (72. 79%). Four symptom groups were extracted by exploratory factor analysis, namely emotional symptom cluster, disease symptom cluster, fatigue symptom cluster and digestive tract symptom cluster. Multivariate stepwise regression analysis showed that metastasis, family monthly income, recurrence, expected hospital stay, number of chemotherapy, chemotherapy regimen, tumor staging and work status were the influencing factors of symptoms. Conclusion There are many symptoms in gynecological cancer patients during chemotherapy. Clinical nurses should start from the point of view of symptom cluster, and provide effective symptoms management measures for patients, to improve their quality of life. (目的 调查妇科恶性肿瘤化疗患者的相关症状, 探讨其症状群的种类以及影响因素。方法 采用一般资料调查表、中文版安德森症状评估表(MDASI)对430名住院妇科恶性肿瘤化疗患者进行调查。结果 妇科恶性肿瘤化疗患者存在多个症状, 症状发生率排名前3位为呕吐(91. 86%)、瞌睡(90. 70%)和疲劳(90. 00%)。症状困扰发生率排名前3位为行走(76. 74%)、人际(76. 30%)、情绪(72. 79%)。探索性因子分析提取出4个症状群, 分别为情绪症状群、疾病症状群、疲乏症状群和消化道症状群。多元逐步回归分析显示肿瘤转移、家庭人均月收入、是否复发、本次预计住院天数、化疗次数、化疗方案、肿瘤分期和工作状况是症状群严重程度的影响因素。结论 妇科恶性肿瘤化疗患者存在多个症状群, 临床护理人员应从症状群的角度出发, 为患者提供有效的症状管理措施, 提高其生活质量。)